ASUHAN KEBIDANAN KOMPREHENSIF PADA Ny. A G1P0A0 USIA KEHAMILAN 32 MINGGU 1 HARI PERSALINAN, NIFAS, BAYI BARU LAHIR DAN KELUARGA BERENCANA DI KLINIK PRATAMA MANDIRI BERASTAGI TAHUN 2022 - Jenika BR. Pinem (Pusat Riset dan Inovasi Nasional, 2023)
In Pregnancy, childbirth, newborns, postpartum, and family planning are physiological processes; However, if not monitored and managed properly, this physiological process can develop into problems or complications that endanger the health of the mother and baby. Increasing health personnel, including midwives, is needed to participate in supporting the health of pregnant women, postpartum women, postpartum women, family planning and newborn babies. Mrs. A, 33 years old, G1P0A0, 32 weeks pregnant, received this comprehensive obstetric care. The physiological labor process is carried out at 32 weeks 5 days of gestation. After delivery, postpartum and consultation regarding postnatal contraception are carried out physiologically. There is no difference between theory and practice in pregnancy, postpartum and newborns. In the case study Mrs. A, management of midwifery care has been implemented and documented using the SOAP method. The conclusion of this final project report is that there is a difference between the implementation of APN during childbirth between theory and implementation in the field. It is hoped that the care provided can reduce MMR and AKN for mothers and babies.